Ambiguitas Kemitraan dan Prekarisasi Kerja Digital, Host Live Streaming Dalam Dinamika Kapitalisme Platform di Indonesia - Usriya Fara Nabila; Moh. Ja’far Sodiq Maksum; Roosmarrani Setiawati (Management and Education Journal, 2026)
Digital transformation through the platform economy has blurred the boundary between workers and entrepreneurs. In live streaming commerce, hosts are positioned as independent partners with flexibility but remain structurally subordinated through data-driven control. This study analyzes the position of live streaming hosts from a sociology of work perspective by integrating the ideas of Karl Marx, Max Weber, and Karl Polanyi. The research uses a qualitative normative-critical approach based on interdisciplinary literature and regulatory analysis. The findings show that platform partnerships represent a reorganization of labor relations in digital capitalism, where algorithmic mechanisms regulate visibility, performance, and income. Work flexibility becomes conditional, while economic risks and system penalties are transferred to hosts. As a result, hosts occupy a liminal position between workers and entrepreneurs but are structurally closer to subordinated labor. These conditions highlight the need for policy intervention that considers the social dimensions of digital work and principles of social justice.